Dendroecologia de Cedrela fissilis (Vell.) na região de Santa Maria, RS - Pereira, Lilian Daniel (2011)
Cedrela fissilis (Vell.) is a species that has a considerable growth and a high quality wood, and because of that it is a potential species for native forests management. However, for the proper handling of this species is necessary the knowledge about its self-ecology and its dynamic in the forest. In order to contribute to the advancement of forest management in Rio Grande do Sul, we sought to evaluate the influence of morphometry (Crown proportion- Pc; range index -IA; degree of slenderness- Hd; salience index - IS; crown formal- FC), of the climate, of the presence of lianas, of soil (granulometry) and the competition (density point of Spurr), in the growing of cedro. Information was collected as regards of: circumference at breast height; overall height , commercial high, insertion height of the canopy; and eight rays of the canopy of dominant cedro trees, besides information about ecological conditions of: density point of Spurr, presence or absence of stones in soil; position on the ground; depth, presence or absence of lianas; and collected soil for particle size analysis. The increment data were obtained by the analysis of two rolls of increments, collected with the use of Pressler borer from. The morphological relationships, of IA, Hd, DBH, and crown diameter explained satisfactorily the average increase in basal area in recent years. The hypsometric relationship and range index were correlated with measures of competition. The growth was not influenced by soil texture. While Liana presence affected the productivity of cedro, trees with presence of lianas yielded less than the others. The growth was influenced by rainfall in November/December to April. The cedro trees in free conditions and with less competition were more suited to the dendroclimatic analysis. The proposed methodology: correspondence of the trend interval, for the formation of dendrochronology average, was more efficient than the methodology for obtaining the dendrochronological series average of the bigger correlations between the baguettes, because the correspondence of the trend interval, beyond include more trees in the dendrochronology mean, had a higher correlation with rain period of November/December to April, improving the correlations of monthly rain, had significant correlation with monthly November, January, march, April, for Spearman correlation with level of significant of 0.05.